Loudness Functions and Binaural Loudness Summation in Bilateral Cochlear Implant Users - Monika NA KORDUS; Jan ŻERA (Archives of Acoustics, 2017)
Loudness functions and binaural loudness summation was investigated in acoustically stimulated bilaterally implanted cochlear implant users. The study was aimed at evaluating growth of loudness functions and binaural loudness summation in cochlear implant subjects as a function of stimulus presentation level at different frequencies. Loudness was assessed using a rating procedure on a scale of 0 to 100. Three experimental conditions were tested: monaural right, monaural left and binaural, each with bands of noise with center frequencies of 0.25, 1, and 4 kHz. Fifteen implanted and five normal-hearing subjects (control group) participated in the experiments. Results demonstrated large variability in the slopes of the loudness functions and the presence of loudness summation in bilateral cochlear implant users, with large individual differences among subjects.